Next generation multiple access for IMT towards 2030 and beyond - Ding, Zhiguo; Schober, Robert; Fan, Pingzhi; Poor, H. Vincent (Science China-Information Sciences, 2024)
NOMA assisted NGMA has been envisioned in the recently published IMT-2030 Framework. This perspective has outlined three important features of NOMA assisted NGMA, namely multi-domain utilization, multi-mode compatibility, and multi-dimensional optimality, where important directions for future research into the design of NOMA assisted NGMA have also been discussed.
CRIS-Team Scopus Importer:2024-10-25